Projetos, faccionalismo e curadoria xamânica: museu feito por ticunas - Ramiro Queiroz Silveira (2015)
This dissertation examines the relationships within the Magüta Museum, created and organized by the indigenous ticuna, in the Brazilian, Peruvian and Colombian borders. Built in Benjamin Constant (in the Brazilian state of Amazonas), in the early 1990s, the institution has its origins in the defense of indigenous rights, especially territorial delineation. Interpretations regarding the Magüta are revised and it points to a current context of factionalism, taking into account political relations among the ticuna. Lastly, alternative hypotheses are suggested, going through production of bodies and care with persons, in contrast with notions of preservation and conservation of material patrimony in traditional museums.